Investigating the Factors Causing Price Differences from Country to Country - Mehwish Channa; Adnan Pitafi; Ghazala Tunio; Asif Ali Shar (CV. Literasi Indonesia, 2022)
This study investigated the factors causing differences in the prices of MNC operating in different countries that affect the pricing in different regions and deviating from the law of one price and influencing factors by comparing prices of both India and Pakistan being developing countries. The study focused on some specific variables such as GDP, exchange rate, purchasing power parity, and price in the dollar that have been analyzed from January 2016 to January 2021 based on biannual data. The quantitative approach has been applied and the study is based on secondary data, Statistics are taken from the “Big Mac Index” which is used as a benchmark for the comparison of the prices to have a deep insight about prices. The product taken for comparison between 2 countries is “The Big Mac” which is a product of McDonald’s (A multinational corporation) that operates more than 36,000 restaurants in more than 100 countries around the world. The tool used for the analysis of the collected data is Microfit software. Results show currency value, Dollar exchange, and Dollar GDP is statistically not significant, in the case of India analysis shows that dollar exchange, dollar GDP, and dollar PPP having values 0.047, 0.004, and 0.011 respectively are significant and currency value 0.458 & dollar price 0.11 are not significant.